2020
DOI: 10.4103/2045-9912.299465
|View full text |Cite
|
Sign up to set email alerts
|

A randomized single-blinded, parallel-arm group feasibility trial evaluating role of pectoral nerve block on serum vascular endothelial growth factor levels in patients undergoing unilateral modified radical mastectomy

Abstract: Metastatic breast cancer cells carry adult and neonatal variants of NaV1.5 voltage-gated activated Na + channels involved in cell invasion. We hypothesize that instilling lignocaine near the surgical field to anesthetize the pectoral nerves for analgesia will decrease angiogenesis by blocking voltage-gated activated Na + channels. Twenty patients undergoing unilateral modified radical mastectomy were randomized in a single-blinded, parallel-arm group feasibility pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Propofol was found to reduce vascular endothelial growth factor, a marker for angiogenesis, during breast surgery; however, no significant short-term effect on breast cancer recurrence was observed ( 72 ) ( Figure 3 ). In a parallel approach, lignocaine administered in the surgical field of a modified radical mastectomy led to decreased angiogenesis markers and better postoperative analgesia ( 73 ). Although anesthesia’s causality of metastatic spread has been thoroughly studied, there remains a lack of conclusive evidence that anesthetic choice and route contribute to cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Propofol was found to reduce vascular endothelial growth factor, a marker for angiogenesis, during breast surgery; however, no significant short-term effect on breast cancer recurrence was observed ( 72 ) ( Figure 3 ). In a parallel approach, lignocaine administered in the surgical field of a modified radical mastectomy led to decreased angiogenesis markers and better postoperative analgesia ( 73 ). Although anesthesia’s causality of metastatic spread has been thoroughly studied, there remains a lack of conclusive evidence that anesthetic choice and route contribute to cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…5 Neshith Govil et al demonstrated that instillation of lignocaine to block the pectoral nerves allows better postoperative analgesia compared to other patients without regional anaesthesia and decreases the secretion of angiogenesis markers, which contributes to tumor generalization. 6 Hip fracture is associated with moderate-to-severe pain, both pre-and post-operatively. Emergent or semi-emergent surgical repair is considered mandatory in most cases.…”
Section: Sp51mentioning
confidence: 99%